Students’ Perceptions of Online Learning in Writing Descriptive Text at MTs Yayasan Pendidikan Jaya Penggalian - Zainul Anwar; Anni Holila Pulungan (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2022)
The purpose of this study was to determine the students' perceptions of online learning in writing descriptive text, which included recognize, make stimuli, experiences, knowledge, motivation, social interaction, understanding, acceptance, responses, and future solutions regarding online learning itself in MTs Yayasan Pendidikan Jaya Penggalian for grade IX, which was done by the English teacher. In this study, a descriptive qualitative research design was used. An English teacher and 27 students who had completed online learning participated in this study. The teacher's utterances and questionnaire answer sheets were used as data sources in this study. The data was gathered through interviews with the teacher and the distribution of a Google Form questionnaire to the online learning students. According to the findings of the interview, Perception related to the The teacher explains English material well through online learning with a percentage of 62,9%. It can be concluded that students' perceptions of online English learning during the Covid-19 pandemic are positive and can be effectively implemented.Keywords: Students’ Perception, Online Learning.